Identifying the Characteristics of Sustainable Design System: A Survey Study - Hossein Basereh Taramsari; Steven Hoffenson; Ashley Lytle; Roshanak Nilchiani (Systems)
To achieve triple bottom line sustainability, a system requires a balance of its social, economic, and environmental axioms. This multi-dimensional system has multiple stakeholders with different objectives acting within the system, leading to an increased level of complexity. Product design is an area with significant potential to achieve sustainable development, which is also influenced by policies. Product designers/managers and policymakers have been identified as critical stakeholders within this complex system, and their decisions directly affect the transition toward sustainable product design. However, these stakeholders have different perspectives on sustainability, and there is a lack of understanding of the main characteristics of a sustainable design system and its requirements. This research aims to find a detailed and unified understanding of these stakeholder’s perspectives, practices, and requirements. An online survey investigated the views of engineers/managers and policymakers in the United States to find their definitions of sustainability, their assessment methods, drivers, and barriers of sustainability. Finally, the participants were asked to identify their requirements for a sustainable design tool that can assist them effectively in designing a sustainable product. Considering the exploratory nature of this study, a targeted sample of 50 participants was selected to capture in-depth, qualitative insights, enabling a nuanced understanding of this complex system. The open-ended questions were designed to obtain detailed responses, which were analyzed qualitatively to develop a comprehensive view of the current state and future requirements for sustainable design tools. This targeted approach allowed the study to probe deeply into each stakeholder’s frame of reference, facilitating the identification of critical factors for a successful transition to sustainable design in both industry and policy. The results identified the critical factors that contribute to a successful transition toward sustainable product design in industry and policies while the requirements found in this study provided a road map to meet the diverse needs of these stakeholders.